ASPEK GRAMATIKAL NOVEL HUJAN KARYA TERE LIYE DAN RELEVANSINYA DALAM PEMBELAJARAN DI SEKOLAH MENENGAH ATAS - Aprilia Kurniawati; Suyitno Suyitno; Slamet Mulyono (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purpose of this study is to describe (1) the grammatical aspects contained in Tere Liye's novel "Rain" and (2) the grammatical aspect of Tere Liye's novel "Rain" which can be used as a learning material in High School XII class. This research includes qualitative research with the main data source is Tere Liye's novel "Rain" by 2017. The characteristic of the novel "Rain" is simple, both simple in the use of language, and simple in the story presented. Sampling technique of this research using purposive sampling. Data analysis technique used is discourse analysis model according to text and context. The results of this study indicate that Tere Liye's novel "Rain" uses the appropriate grammatical aspects so as to form a unified discourse. Grammatical aspects used include references, substitutions, ellipsis and conjunctions. The discourse of "Rain" by Tere Liye has relevance as a novel teaching material at High School because the discourse is presented in simple language and featuring a light storyline.